Critical Consciousness, Te Tiriti o Waitangi and Public Health Education - Christina Severinsen; Angelique Reweti (New Zealand Journal of Teachers' Work)
Aotearoa New Zealand is experiencing a significant shift in political discourse surrounding Te Tiriti o Waitangi. The current government, under the guise of ending ‘race-based’ policies and reducing bureaucracy, is proposing changes that threaten to erode the rights and protections of tāngata whenua [Indigenous people of the land]. While the coalition government asserts its commitment to improving outcomes for all New Zealanders, the changes represent a direct assault on Māori that will disproportionately and negatively impact Māori communities. In this political climate, the role of education becomes even more critical. As educators in public health, our commitment to uphold the provisions and principles of Te Tiriti o Waitangi and to foster understanding is unwavering and more pressing than ever. In this opinion piece, we argue that embedding Te Tiriti o Waitangi meaningfully throughout our curriculum is not just beneficial but essential.